The Dark Triad and sleep quality: Mediating role of anger rumination. (1st December 2019) - Yang, Minqi; Zhu, Xueli; Sai, Xueying; Zhao, Fengqing; Wu, Haofei; Geng, Yaoguo
Abstract: The current study investigated the associations between Dark Triad and scores on the Pittsburgh Sleep Quality Index, and the mediating effect of anger rumination on the relationships between Dark Triad and overall sleep quality in a sample of 560 adults. Men scored significantly higher on narcissism, and lower on use of sleeping medication than women did. Correlations revealed that Machiavellianism, primary, and secondary psychopathy, were significantly associated with poor sleep quality and greater anger rumination, whereas narcissism was neither associated with overall sleep quality, nor with anger rumination. Mediating effect analysis revealed that (1) Machiavellianism was directly associated with poor sleep quality, as well as indirectly associated with poor sleep quality via greater anger rumination; (2) both primary and secondary psychopathy were indirectly associated with poor sleep quality via greater anger rumination, and secondary psychopathy had the strongest direct effect on poor sleep quality among the Dark Triad. These results give further support to the overlapping but distinct nature of the Dark Triad, and provide insight into the behaviors and underlying psychological processes associated with the Dark Triad.